Jacoby, Melissa B. Unjust Debts: How Our Bankruptcy System Makes America More Unequal - Admati, Anat R. (Journal of Economic Literature, 2025)
Anat R. Admati of Stanford University reviews “Unjust Debts: How Our Bankruptcy System Makes America More Unequal” by Melissa B. Jacoby. The Econlit abstract of this book begins: “Explores the impact of the bankruptcy system, promoting the argument that the present structure of reorganization cases has compromised policy objectives distant from bankruptcy's intended domain.”